2003
DOI: 10.1128/jvi.77.10.6066-6069.2003
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference of Human Papillomavirus Type 18 E6 and E7 Induces Senescence in HeLa Cells

Abstract: The human papillomavirus oncoproteins E6 and E7 promote cell proliferation and contribute to carcinogenesis by interfering with the activities of cellular tumor suppressors. We used a small interfering RNA molecule targeting the E7 region of the bicistronic E6 and E7 mRNA to induce RNA interference, thereby reducing expression of E6 and E7 in HeLa cells. RNA interference of E6 and E7 also inhibited cellular DNA synthesis and induced morphological and biochemical changes characteristic of cellular senescence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
161
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(174 citation statements)
references
References 17 publications
(19 reference statements)
12
161
1
Order By: Relevance
“…Knock down of E6 and E7 protein by RNA interference could induce senescence in HeLa Cells 30. Consistently, we observed that HeLa cells occurred senescence when the integrated HPV fragment was removed.…”
Section: Discussionsupporting
confidence: 83%
“…Knock down of E6 and E7 protein by RNA interference could induce senescence in HeLa Cells 30. Consistently, we observed that HeLa cells occurred senescence when the integrated HPV fragment was removed.…”
Section: Discussionsupporting
confidence: 83%
“…Whereas, we specifically target E6 by RNAi, treatment with IP10 resulted in the inhibition of both E6 and E7 expression. Yet, in contrast to studies indicating that combined E6 and E7 inhibition primarily results in senescence (Goodwin et al, 2000;Wells et al, 2000;Hall and Alexander, 2003), induction of apoptosis was reported. In addition, IP10 is likely to exert additional biological activities besides affecting E6/E7 expression.…”
Section: Discussioncontrasting
confidence: 65%
“…E6 targets the PUMA/Bax Pathway M Vogt et al inhibition of E6 and E7. The combined inhibition of E6 and E7 primarily leads to growth arrest and senescence (Goodwin et al, 2000;Wells et al, 2000;Hall and Alexander, 2003), due to the release of pRb from the inhibitory influence of E7 (Psyrri et al, 2004). However, if growth arrest cannot be induced -due to the sustained inactivation of pRb-associated pathways by E7 -inhibition of E6 alone will result in Bax-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the complex pattern of the polycistronic E6/ E7 mRNAs that are transcribed from chromosomally integrated HPV genomes in cervical cancer cells, it is possible to generate siRNAs that either block E6 expression alone or E6/ E7 expression in combination. 20,35 The selective inhibition of E6 by RNAi is linked to induction of apoptosis. 20 As exosome preparations can be contaminated by material coming from apoptotic cells, 30 which can lead to data misinterpretation, 45 we focused on the combined silencing of viral E6 and E7 expression by RNAi.…”
Section: Discussionmentioning
confidence: 99%